Distribution of macrobenthic fauna in Phawong and U-Taphao canals flowing into a lagoonal lake, Songkhla, Thailand - S., Angsupanich (Lakes & Reservoirs: Research and Management, 2016)
The macrobenthic fauna of two discharge ecosystems, Phawong Canal and U-Taphao Canal flowing into Songkhla Lake in Thailand, were studied from August 1994 to August 1995. The salinity of Phawong Canal and U-Taphao Canal ranged from 0.1 to 27.8 and 0.1 to 17.0 practical salinity units (PSU), respectively. The biochemical oxygen demand (BOD) of Phawong Canal ranged from 2.5 to 33.0mg L21, while that of U-Taphao Canal ranged from 1.1 to 12.6mgL21. Temporal changes in the number of species and individuals were determined throughout a year. During the season of heavy rains (November-December), the density and number of most species decreased markedly. Only chironomid larvae increased and these were distributed in the uppermost reaches of the canals during this period. Sixty-two and 52 species of macrobenthic fauna were found in Phawong Canal and U-Taphao Canal, respectively; however, the abundance and number of species collected at each sampling was very low in the upper reaches of the canals. The most numerous benthic fauna in the Phawong Canal were polychaetes, followed by amphipods. Pelecypods and gastropods were the dominant groups in U-Taphao Canal. A distribution pattern of macrobenthic fauna associated with pollution gradients (BOD) was observed only at Phawong Canal. In addition, species diversity according to the Shannon-Wiener index only was not applicable to the assessment of benthic environmental health when the few individuals found were evenly distributed among the few species present at U-Taphao Canal. It is recommended that a coastal care project be established by the appropriate government agencies in the study areas.